Paternal effect on genomic activation, clinical pregnancy and live birth rate after ICSI with cryopreserved epididymal versus testicular spermatozoa - Goldfarb James; Sabanegh Edmund; AbdelHafez Faten; Desai Nina (BMC, 2009)
Abstract Background This study takes an in depth look at embryonic development, implantation, pregnancy and live birth rates with frozen epididymal and testicular sperm from obstructed (OA) and non-obstructed (NOA) patients. Methods Paternal effect of sperm source on zygote formation, embryonic cleavage, and genomic activation were examined. Additional outcome parameters monitored were clinical pregnancy rate (CPR), implantation rate (IR) and live birth rate. Results In this report, we retrospectively analyzed 156 ICSI cycles using cryopreserved epididymal sperm (ES; n = 77) or testicular sperm (TESE; n = 79). The developmental potential of embryos did not appear to be influenced by the type of surgically retrieved sperm. The average number of blastomeres observed on Day 3 was not different among different groups; 7.5 +/- 1.7 (ES), 7.6 +/- 2.1 (TESE-OA) and 6.5 +/- 2.3 (TESE-NOA). Compaction and blastulation rates, both indicators of paternal genomic activation, were similar in embryos derived from ICSI with ES or TESE from OA as well as NOA men. The only parameter significantly affected in NOA-TESE cases was the fertilization rate. CPR and IR with cryopreserved TESE (TESE-OA 59%, 34%, and TESE-NOA 37%, 20%) were also not statistically different, from that achieved with cryopreserved ES (61% and 39%). Live birth rates also appeared to be independent of sperm type. The 87 clinical pregnancies established using cryopreserved TESE and ES, resulted in the birth of 115 healthy infants. No congenital anomalies were noted. Conclusion Zygotic activation seems to be independent of sperm origin and type of azoospermia.